Rola i znaczenie instytucji zmiany sposobu wykonywania zakazu prowadzenia pojazdu w świetle art. 182a k.k.w. - Włodarczyk, Magdalena; Kalisz, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The article deals with one of the fundamental principles of executive criminal law, which is the principle of modifying penalties and measures in executive proceedings. The art. 182a of the Penal Code thus makes it possible to ease the repressive nature of the previously imposed measure of a criminal prohibition on driving. The penal measureof a driving ban after a court ruling is still being enforced. Nevertheless, it is no longer absolute, as its scope is limited only to vehicles not equipped with an alcohol interlock. For many perpetrators of traffic crimes with the imposed penal measure of prohibiting driving vehicles this institution has become a chance — for some the only one — to drive vehicles despite the ban imposed by the court.
Keywords: penal measure; driving ban; alcohol interlock